Constitutional Determinants of Government Spending - Guido Tabellini (Center for Economic Studies and ifo Institute (CESifo), 2000)
This paper surveys some recent literature on fiscal policy and comparative politics. Economic policy is viewed as the outcome of a game with multiple-principals and multiple-agents. Opportunistic politicians bargain over policy. Rational voters hold them accountable through retrospective voting. Political institutions determine the rules for legislative bargaining and for electing politicians to office. The questions asked are: how do alternative electoral rules and alternative regime types shape the size of government, the composition of spending, the performance of politicians in terms of effort or corruption, the features of electoral cycles. The paper discusses both theory and evidence, and concludes with some speculations about directions for future research.
Keywords: 330; Comparative politics; corruption; elections; fiscal policy